Effect of Gamma Rays on Some Stages of Development of Rhyzopertha dominica (Fab.) (Baghdad Science Journal, 2009)
The effect of different doses of gamma rays that emitted from 60Co on the development of different stages of lesser grain borer Rhyzopertha dominica (Fab.) was investigated . The results showed that the eggs in both early (1-3 days) and late (7-9) old were very sensitive to gamma rays and its hatch was zero at 10 Gy for both ages in comparison with 83.3% for the control group. Furthermore, the results illustrated that the larval stage in its two old ages were different in the radiosensitivity, the percent of its death were 100% & 96.6% when they exposed to 100 & 120 Gy, respectively. Moreover, the results showed that the sensitivity of pupal stage at age of 1-3 days was increased with increasing the doses of gamma rays, the percent of normal adults eclosed from irradiated pupae was 83.3% at the dose of 20 Gy and it became 3.3% at the dose of 200 Gy in comparison with that of the control treatment which was 93.3%.